Implementation of hybrid simulation training to promote collective and self-efficacy in medical students: a two-pronged approach - Calvin Yuk Wang Tam; John Ian Wilzon T. Dizon; Simon Wai Ching Sin; Gloria Kai Yan Tang; Victor Yuk Wah Lai; Yvonne Yin Wong; Fraide A. Ganotice; Pauline Yeung Ng (Annals of Medicine, 2025)
Introduction Simulation-based training (SBT) is an integral and indispensable component of medical and healthcare education, especially pertinent in acute care. Conventional forms of SBT in acute care primarily involve manikins or task trainers, which are either costly or too task-specific. Recent innovations in virtual patient simulation software (VPS) invites the opportunity for conjoined use with basic manikins, creating a hybrid model for acute-care teaching. This study aimed to: ① Assess the impact of hybrid simulation teaching on the collective efficacy (CE) and self-efficacy (SE) of medical students, and ② evaluate psychometric measurement scales within the simulation context.Methods A prospective cross-sectional cohort study was conducted between 22 September 2023, and 19 December 2023. Fifth year medical students in an undergraduate medicine program underwent hybrid SBT, incorporating VPS and basic manikin within two separate clinical scenarios. Primary outcome of CE and SE was measured using adapted versions of the Perceived Collective Efficacy (PCE) scale and Motivational Strategies for Learning Questionnaire (MSLQ). Both scales were distributed to students before and after undergoing hybrid SBT.Results Data from 94 students were available for pairwise testing. Significant improvements were observed in the CE and SE of students after undergoing hybrid SBT [CE: (12.16 ± 3.86 vs 15.42 ± 2.87); p < 0.001]; [SE: 24(23–32) vs 32(28–34); p < 0.001]. Scale evaluation of Perceived Collective Efficacy (PCE) and Motivational Strategies for Learning Questionnaire (MSLQ) revealed good scale Cronbach α scores [PCE: pretest α = 0.929; posttest α = 0.914]; [MSLQ: pretest α = 0.971.; posttest α = 0.968].Conclusion Hybrid SBT facilitated by virtual patient simulator and basic manikin provides a moderate-cost and adaptable approach which positively impacted the CE and SE of medical students. As software development readily adapts in providing point-of-care learner feedback, hybrid SBT should become more widely implemented to fully harness its potential.